Discriminating Fake From True Brain Injury Using Latency of Left Frontal Neural Responses During Old/New Memory Recognition - Neal, Jennifer; Strothkamp, Stephanie; Bedingar, Esias; Cordero, Patrick; Wagner, Benjamin; Vagnini, Victoria; Jiang, Yang (Frontiers in Neuroscience, 2019)
Traumatic brain injury (TBI) is a major public health concern that affects sixty-nine million individuals each year worldwide. Neuropsychologists report that up to 40% of individuals undergoing evaluations for TBI may be malingering neurocognitive deficits for compensatory reward. The current memory recognition test of malingering detection is effective but can be coached behaviorally. We developed a method measuring latency of neural responses in milliseconds for discriminating true TBI from malingerers who fake brain injury. We test the hypothesis that decision making of malingered memory recognition deficits prolongs neural responses during memory recognition. To test this hypothesis, latencies of memory-related brain potentials were compared among true patients with moderate or severe TBI, healthy age-matched individuals who were assigned either to be honest or faking memory deficit. Scalp signals of electroencephalography (EEG) were recorded with a 32-channel cap during an Old/New memory recognition task in three age- and education- matched groups: honest (n=16), malingering (n=16), and brain injured (n=15) individuals. An event-related potential (ERP) component P3 during memory recognition was analyzed using EEGLAB. Bilateral P3 fractional latencies of frontal scalp sites were compared among the three groups under both studied (Old) and New memory recognition conditions. Results show a significant difference in P3 fractional latencies during recognition of studied items in malingerers (averaged latencies = 396 ms) when compared to true brain injured subjects (mean = 312 ms) in bilateral frontal sites. Significant delayed P3 latencies were also found during recognition of studied items in malingerers when compared to honest subjects in bilateral frontal electrodes. There was no significant difference in any group for recognition of New items. These results, along with previous reported delay in reaction times (Vagnini et al., 2008), indicate that additional processing time in frontal activity of malingering individuals are measurably different from those of actual patients with brain injury.